Vanuatu : 2021 Article IV Consultation -Press Release; Staff Report; and Statement by the Executive Director for Vanuatu. (IMF Staff Country Reports; Country Report ;, 2021)
Border closures and other pandemic containment measures have kept Vanuatu free from COVID-19. However, they have dealt a heavy blow to economic activity as tourism has come to a virtual halt. On top of the pandemic, Tropical Cyclone Harold and a volcanic eruption in Tanna Island caused extensive economic damage in 2020. In the context of a continued loss of correspondent banking relationships (CBRs) in the Pacific, Vanuatu also lost a key CBR at end-June 2021. Air Vanuatu, one of the state-owned enterprises (SOEs), is in the process of being restructured.